Legal Analysis of Press Responsibility in A Democratic Country from The Perspective of Four Press Theories (Review of the Theories Of Fred S. Siebert, Theodore Peterson, and Wilbur Schramm) - Joko Susanto; Darma Wijaya Maulana; Redentor Goncalinho Antonio Obe; Royce Wijaya Setya Putra (PT Syamilah Literasi Islami, 2024)
This article discusses the legal analysis of press responsibility in a democratic country from the perspective of four press theories, namely Fred S. Siebert, Theodore Peterson, and Wilbur Schramm. The study was conducted with the aim of understanding the concept of press responsibility in the context of a democratic country. The method used is a comparative descriptive analysis of the four press theories. The results of the study indicate that press responsibility in a democratic country has several dimensions that need to be considered, including press freedom, journalistic ethics, and self-control. Siebert's Press Theory emphasizes the importance of social control over the mass media, while Peterson's theory focuses on the role of journalists as guardians of the truth. On the other hand, Schramm's theory emphasizes the relationship between the media and society. From the results of this analysis, it is concluded that press responsibility in a democratic country must be accommodated by freedom of opinion, media diversity, and public participation in the decision-making process. The implication of this study is the need for a holistic understanding of press responsibility as the main pillar in maintaining the balance of information and power in a democratic society.